Benchmarking Energy Use towards Systematic Energy Management in Commercial Bank Branch - Tantiwanit, Kornkamon (Journal of Architectural/Planning Research and Studies (JARS), 2018)
This paper presents the study of energy consumption benchmark for a specific type of office building, commercial bank branch. The data including physical information and energy consumption were collected from 44 buildings of commercial bank branch. It shown that energy consumption is 61.5% significantly related to air-conditioned area, and the average of annual energy consumption is 137,539 kWh/year. Moreover, the average of annual energy consumption per area, so called Energy Use Index (EUI), is 306.31 kWh/m2/year. According to percentile distribution, the 50th percentile was found as 285.17 kWh/m2/year. At the end of paper, the application for evaluating energy use and setting up energy target towards energy conservation and energy management in building was proposed.